Drug‐induced immune‐mediated thrombocytopenia secondary to durvalumab use. Issue 6 (22nd June 2021) - Dougherty, Sean C.; Lynch, Alia C.; Hall, Richard D.
Abstract: Immunotherapy is an expanding area of cancer treatment with significant promise. Despite their efficacy, checkpoint inhibitors are associated with a number of immune‐related adverse events; here, we described thrombocytopenia secondary todurvalumab. Abstract : Immunotherapy is an expanding area of cancer treatment with significant promise. Despite their efficacy, checkpoint inhibitors are associated with a number of immune‐related adverse events; here, we described thrombocytopenia secondary todurvalumab.